Evaluasi Pasca Pelatihan Pada Pelatihan Penugasan Khusus Tenaga Kesehatan Berbasis Tim (Tugsus) di Puskesmas Tahun 2024: Post-Training Evaluation of Team-Based Special Assignment (Tugsus) at Primary Health Centers in 2024 - Rahman, Fauzi; Anisah, Ani; Prameswari, Kania (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
Indonesia faces significant challenges with the uneven distribution of human resources for health (HRH), especially in Disadvantaged, Border, and Outermost Areas (DTPK). To address this, the Ministry of Health launched the Team-Based Special Assignment (Tugsus) program, supported by targeted training for health workers. This study aimed to evaluate the implementation of this training after its completion, focusing on the relevance of the training materials, their application in the field, and the impact of Tugsus teams on the performance of Primary Health Centers (PuskesmasThis study employed a cross-sectional evaluation design conducted in a single data collection phase. The approach used was a mixed method, combining qualitative and quantitative approaches, the study was conducted from April 28 to May 07, 2025. Data were gathered via online questionnaires 188 of 240 program alumni (Batches 27-29), 33 supervisors, and 59 colleagues. Results indicate that the training materials are highly suitable (average 91. 31%) for practical needs and are widely applied (average 94. 33%). The highest application rates are seen in soft skills, such as Coaching (98. 40%), and routine activities, like Posyandu (99. 47%). In contrast, application of systemic topics, such as Accreditation (85.64%), is somewhat lower. The presence of Tugsus teams shows a significant positive effect, mainly by filling critical HRH gaps. However, a gap remains between the ideal concepts taught during training and the realities faced in the field, primarily due to structural barriers like limited local HR and facilities. The evaluation results show that this training provides participants with relevant competencies, but to enhance the program's future impact, there should be a focus on strengthening the capacity of the Puskesmas system to adopt innovations, rather than solely emphasizing individual competencies. Keywords: Post-Training evaluation; Team-Based special assignment; Primary health center.